Data availability issues: decisions as patterns of action. (15th December 2022) - Wibisono, Arif; Sammon, David; Heavin, Ciara
ABSTRACT: This research investigates how an organisational unit organises workaround-centric data activities (WCDA) to cope with data availability issues (in the context of their centralised and decentralised systems landscape). To unpack these often-invisible WCDA patterns of action, we present a field study of a Quality Assurance (QA) unit of an Indonesian sugar plantation company. We use open coding and a narrative network (NN) approach to complete our analysis. Our findings reveal that data availability issues produce three patterns of action: dual inspection, prudent control, and mindful handling. An organisation can build plausible pictures for governing data by better understanding these visualised patterns. Lastly, we discuss the pros and cons of these patterns of action in the context of data governance.